2019
DOI: 10.1055/s-0039-1697623
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Cartilage Lesion in the Lateral Compartment of the Knee on the Surgical Outcome of Medial Open-Wedge High Tibial Osteotomy

Abstract: The aim of this study was to identify the effect of cartilage lesion in the lateral compartment of the knee on the surgical outcome of medial open-wedge high tibial osteotomy (MOWHTO). A total of 172 consecutive patients who underwent MOWHTO were evaluated retrospectively. Among the patients who underwent second-look arthroscopic assessment, 30 patients with lateral compartment cartilage lesion (group 1: ≥ grade 2 cartilage lesion according to the International Cartilage Repair Society [ICRS] grading system) a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
19
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(19 citation statements)
references
References 29 publications
0
19
0
Order By: Relevance
“…Four comparative studies and two case series were included [ 31 , 32 , 51 54 ]. The baseline characteristics and patient demographic details are presented in Table 1 .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Four comparative studies and two case series were included [ 31 , 32 , 51 54 ]. The baseline characteristics and patient demographic details are presented in Table 1 .…”
Section: Resultsmentioning
confidence: 99%
“…Despite favorable outcomes following concurrent MMPRT repair during HTO, no randomized controlled studies or large-scale cohort studies have been published [ 31 , 32 ]. To clarify the treatment effects using objective numerical values, a systematic review and meta-analysis of all available case series or comparative studies on concurrent MMPRT repair during HTO is required.…”
Section: Introductionmentioning
confidence: 99%
“…9 There have been some clinical studies conducted on cartilage lesions in the lateral compartment. 21,22 Niemeyer et al 22 reported that the clinical outcomes of patients with partialthickness cartilage lesions in the lateral compartment after OWHTO were not different from those of patients with completely intact cartilage in the lateral compartment. The follow-up period of their study was about 36 months.…”
Section: Discussionmentioning
confidence: 99%
“…The follow-up period of their study was about 36 months. Moon et al 21 reported that the presence of ICRS grade 2 or 3 cartilage lesions in the lateral compartment did not affect the outcomes of OWHTO after roughly 23 months of follow-up. However, these studies only evaluated outcomes according to the cartilage status of the lateral compartment.…”
Section: Discussionmentioning
confidence: 99%
“…As such, the aim was to investigate whether these patients can achieve comparable results to patients with normal lateral knee compartments and thus can be regarded as equally indicated for HTO. Some studies suggest that asymptomatic mild to moderate focal cartilage defects of the lateral compartment can be very well accepted without negatively in uencing the total bene t of the HTO procedure [34,35].…”
Section: Discussionmentioning
confidence: 99%